Penyeliaan, gaji dan persekitaran kerja mempengaruhi kepuasan kerja dalam kalangan pekerja kumpulan sokongan di ibu pejabat JKR Negeri Kedah - Suhana, Ismail (2020)
Job Satisfaction is an important aspect for every organization. The main aim of this study was to examine the influence of supervision, salary and work environment on job satisfaction toward employees. The study involved 111 employees among the support group based at JKR headquarters Negeri Kedah. This is a quantitative research. Data collected were analysed using the Statistical Package for Social Science (SPSS) version 24.0 to determine the relationship between the independent variables which were supervision, salary and work environment with the dependent variable which is job satisfaction. Based on the findings, supervision and salary influenced job satisfaction positively but work environment, did not influence job satisfaction. Finally, the organization should play a significant role in order to keep their employee satisfied because it may bring so many benefits to the organization. The researcher will provide a recommendation to the organization at the end of this study.